Shall Wagnerism have no Dominion? - Tucker, Eric (Just Labour, 2014)
The Wagner Act Model has formed the basis of Canada ’s collective bargaining regime since World War II but has come u nder intense scrutiny in recent years because of legislative weakening of co llective bargaining rights, constitutional litigation defending collective barg aining rights and declining union density. This article examines and assesses t hese developments, arguing that legislatively we have not witnessed a wholesal e attack on Wagnerism, but rather a selective weakening of some of its element s. In the courts, it briefly appeared as if the judiciary might constitutionaliz e meaningful labour rights and impede the erosion of Wagnerism, but recent judicia l case law suggests the prospects for this outcome are fading. While the po litical defence of Wagnerism may be necessary when the alternatives to it are li kely worse, holding on to what we’ve got will not reverse the long-term decline in union density. The article concludes that at present there are no legal soluti ons to the labour movement’s problems and that innovative efforts to represent w orkers’ collective interests outside of formal collective bargaining provide a m ore promising alternative.